Analisis Proses Pembuatan Tujuan Pembelajaran Berdasarkan Capaian Pembelajaran pada Kurikulum Merdeka Kelas 4 SDN Karang Anyar 2 - Magdalena, Ina; Nurjanah, Fitria; Afiyah, Azzahra Dhiya (YASIN, 2023)
In the course of the history of curriculum development, Indonesia has experienced several curriculum changes. One of the curriculum development products currently used is an independent curriculum policy. The main requirement for the implementation of curriculum policies is the construction of solid curriculum knowledge. As a result, activities designed to educate teachers about the curriculum aim to educate teachers and increase their understanding of the subject. The independent curriculum, which includes the operational curriculum as well as the instructional curriculum, is the focus of the educational objective material. Teachers at SDN Karang Anyar 2 participated in this activity. The results of the activity show that it really helps teachers understand how to implement an independent curriculum as a national curriculum by providing information and expanding their knowledge about the curriculum.